Model of Development of Self-determination as the Basis of Prevention of Addictive Behavior of Adolescents in Contemporary Educational Organizations - Stepanova N.A., (Психолого-педагогические исследования, 2018)
The article presents the analysis of the current domestic research of the problem of self-determination. It is shown that adolescence is a sensitive period for the development of self-determination, but there are not enough studies of its dynamics at this age and ways of the formation. Self-determination is considered in the article as the opposite of addictive behavior, which makes it a resource in terms of prevention of pathological dependencies. Therefore, the proposed approach to optimization of the system of prevention in educational institutions through the development of self-determination in adolescence, based on the development of the spiritual fulfillment of the individual as the main stage of formation of the self. A model of interaction between education experts in the course of prevention of addictive behavior in educational organizations, reflecting the main stages of development of self-determination in the course of maintenance work.